RECONSTRUCTING THE INSTITUTIONALIZATION OF POLITICAL PARTIES IN THE STATE OF LAW AND DEMOCRACY - Miuttaqin, Imam Choirul (NOMOI Law Review, 2023)
One of the functions of political parties is political recruitment. In this function, political parties are an institution for the selection process in the context of filling public or political positions. As the main actor in democracy, democracy should start from within the party itself based on true participation from its members. What is meant is that the function of political recruitment and supplier of public positions (legislative and executive) must be based on a mechanism based on participation and deliberation of its members (internal democracy of political parties) . The method used in this research is normative juridical law research method. Internal democracy is not only the contestation for the election of general chairman or political party administrators in congresses, conferences and the like, but also the phenomenon of well-known legislative candidates such as artists, rich people or media bosses and the like can result in jumping into political office through parties. Strengthening the institutionalization of political parties is carried out in at least four ways, namely first, conditioning the formation of a simple multiparty system, second, encouraging the creation of democratic and accountable party institutionalization, third, conditioning the formation of democratic and accountable party leadership and fourth encouraging the strengthening of the party base and structure in community level.